Feiras livres: limites e possibilidades para o desenvolvimento rural sustentável - Cruz, Raphael Miranda Medeiros (2019)
This research addresses within the social conjuncture of family farming and its productive system, the interface a new distributive economic alternative, its pluriactivity and rural tourism of events as an alternative for sustainable rural development, found that rural fairs strengthen the links between urban and rural. and the main subject the farmer through family farming finds a great opportunity for economic strengthening in the local Market. This dissertation aims to analyze the free fairs with the participation of Family Farming held in the municipalities Lindeiros to Lake Itaipu, in relation to sustainable rural development. In this perspective, it is proposed to draw a historical profile of the free markets of the region under study, identify among the 17 objectives of sustainable development (SDG), which fit the object of study and promote the sustainable development of the region Lindeira to Lake Itaipu. This is an analytical study supported by the descriptive and statistical exploratory documentary bibliography that addresses the relationship between sustainability, rural development, family farming and rural fairs, more precisely the free fairs in the urban environment, complemented by field research using a structured questionnaire. with open and closed questions for producers and organizers, using the Likert scale with rural exhibitors. Thus, using documentary information and interviews in the form of a questionnaire with the exhibitors and organizers, it was successful in the results found. The fair can also be considered as a business alternative for family farming and rural tourism, acting as a propeller for sustainable rural development, since it generates income and expands the opportunity to offer traded products, bringing not only financial return. , as well as social and environmental for the small farmer.